Computing Directed Pathwidth in O(1.89n) Time - Kitsunai, Kenta; Kobayashi, Yasuaki; Komuro, Keita; Tamaki, Hisao; Tano, Toshihiro (Algorithmica, 2016)
We give an algorithm for computing the directed pathwidth of a digraph with n vertices in O ( 1 . 89 n ) time. This is the first algorithm with running time better than the straightforward O ∗ ( 2 n ) . As a special case, it computes the pathwidth of an undirected graph in the same amount of time, improving on the algorithm due to Suchan and Villanger which runs in O ( 1 . 9657 n ) time.